A DISCUSSION ON FORM OF ALLUSIONS AND ITS CONNECTION TO SOCIAL CHANGES IN A SATIRICAL PLAY, EASTWARD HO - Sistiadinita Sistiadinita (STBA Pontianak, 2019)
Since its first performance in 1605, Eastward Ho had heightened public interest by giving audience a taste of entertaining, satirical play set around the life of Touchstone, a hard-working and honest goldsmith. The play depicts the conflict between contrasting figures: Touchstone’s daughters – the ambitious Gertrude and the obedient Mildred – and his apprentices – the prodigal Quicksilver and the faithful Golding. These strong characters have driven intriguing plots into an ending where each side receives what he or she deserves. This story describes the characters of urban masculinity as well as female attitudes towards social status, class, and property. A moralistic view is developed in a conventional, yet entertaining way, where the line between virtue and vice can be distinctly discerned. This is one of the characteristics of the period and predominantly reflects the authors’ viewpoints. Created by three prominent playwrights; Ben Jonson, John Marston and George Chapman as a collaborative task, some portions of Eastward Ho are alluded to in well known titles, places, characters, proverbs and lines, of previous works near the period. This essay therefore tries to explore the social changes of the play by its various forms of allusions.